Corruption and Economic Growth in West Africa - Ighodaro, Clement Atewe; Igbinedion, Sunday Osahon (JEJAK: Jurnal Ekonomi dan Kebijakan, 2020)
The level of corruption in West Africa has become very worrisome based on the data from the corruption perception index of transparency international. Corruption may subvert due process; reduce accountability; lead to unequal distribution of goods and services and limit the reliance of the masses on government. The objective of the paper was to examine the link between corruption and economic growth in West Africa. Data used span from 2000 to 2018 with a cross section of fifteen West Africa countries and the use of panel fully modified ordinary least squares. With the use of the Im, Pesaran, and Shin stationarity which allows for heterogeneous version of the Dickey Fuller test, it was found that the variables used were integrated of order one and long run equilibrium relationship existed based on the Pedroni cointegration method. Only foreign direct investment did not meet the a priori expectation. The result supports the ‘grease on the wheel hypothesis’. This implies that corruption and economic growth have direct relationship in West Africa. Corruption and economic growth were found to also support the U-shaped hypothesis which means that different corruption level affect economic growth in different ways. However, corruption does not lead to efficient and effective outcomes hence should not be allowed at any level of governance.